Justice Versus Certainty: The Antinomy of Law in the New Indonesian Criminal Code from the Perspective of Radbruch's Formula - Rahmanu Wijaya; Ade Putra Hasibuan (Universitas Negeri Surabaya, 2025)
The ratification of the new Criminal Code in Indonesia, while aiming to reform criminal law, also presents legal issues, particularly from a legal philosophical perspective. This is as stated in Article 53 paragraph (2) of the New Criminal Code, which accommodates the Radbruch formula, potentially leading to judicial bias and case manipulation due to subjectivity in prioritizing justice over legal certainty. This research is normative legal research that prioritizes philosophical, conceptual, and legislative approaches. The research findings confirm the essence of the Radbruch formula in Indonesian legal and criminal philosophy, which emphasizes the supremacy of the value of justice over legal certainty in conditions of value conflict. Article 53 paragraph (2) of the New Criminal Code, which accommodates the Radbruch formula, needs improvement and legal renewal to avoid judicial arbitrariness in criminal law enforcement. Therefore, it is necessary to renew and perfect Article 53 paragraph (2) of the New Criminal Code through norm revision or judicial review to maintain the constitutionality of the article and achieve a balance between legal certainty and objective justice in the Indonesian criminal justice system.